2016
DOI: 10.1097/tp.0000000000000785
|View full text |Cite
|
Sign up to set email alerts
|

Portal Vein Thrombosis Is a Risk Factor for Poor Early Outcomes After Liver Transplantation

Abstract: Portal vein thrombosis at LT is associated with early (90 days) mortality and graft failure, though a likely but undefined reporting bias for more extensive PVT would overstate estimated risks for all PVT. Further study is needed to better define risks of LT with PVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(48 citation statements)
references
References 18 publications
3
43
0
2
Order By: Relevance
“…Also other series reported a significant higher first 3 months perioperative mortality and graft failure in patients with pre-existing PVT mainly in patients with extensive PVT [24,25].…”
Section: Discussionmentioning
confidence: 87%
“…Also other series reported a significant higher first 3 months perioperative mortality and graft failure in patients with pre-existing PVT mainly in patients with extensive PVT [24,25].…”
Section: Discussionmentioning
confidence: 87%
“…Even though PVT is no longer considered a contraindication in LT [5, 6], it remains a risk factor associated with posttransplant morbidity and mortality, directly affecting graft patency [1014]. Technical difficulties increase surgery time and lead to severe bleeding; inadequate blood flow may result in graft disfunction or loss and rethrombosis [3, 12, 13, 1520]. …”
Section: Discussionmentioning
confidence: 99%
“…PVT in patients with cirrhosis has been shown to have little influence on the course of liver disease, except for patients with PVT at liver transplantation in whom 90-day mortality and graft failure have been reported to be higher than in those without PVT [10,11]. Moreover, non-progression or resolution has been reported in up to 75% of patients.…”
Section: Definitions and Classificationmentioning
confidence: 99%
“…Extensive PVT has been shown to be associated with higher mortality after liver transplantation, while incidentally discovered PVT during liver transplantation did not affect mortality [67,70]. However, studies found that complete PVT impacts short-term survival (3 months to 1 year), whereas long-term survival does not differ between PVT and non-PVT groups [41,71,72]. This effect might be due to the surgical techniques available for portal anastomosis depending on the extent of PVT.…”
Section: Prognosismentioning
confidence: 99%